Investigation of PBL schemes combining the WRF model simulations with scanning water vapor differential absorption lidar measurements. Issue 2 (19th January 2016) - Milovac, Josipa; Warrach‐Sagi, Kirsten; Behrendt, Andreas; Späth, Florian; Ingwersen, Joachim; Wulfmeyer, Volker
Abstract: Six simulations with the Weather Research and Forecasting (WRF) model differing in planetary boundary layer (PBL) schemes and land surface models (LSMs) are investigated in a case study in western Germany during clear‐sky weather conditions. The simulations were performed at 2 km resolution with two local and two nonlocal PBL schemes, combined with two LSMs (NOAH and NOAH‐MP). Resulting convective boundary layer (CBL) features are investigated in combination with high‐resolution water vapor differential absorption lidar measurements at an experimental area. Further, the simulated soil‐vegetation‐atmosphere feedback processes are quantified applying a mixing diagram approach. The investigation shows that the nonlocal PBL schemes simulate a deeper and drier CBL than the local schemes. Furthermore, the application of different LSMs reveals that the entrainment of dry air depends on the energy partitioning at the land surface. The study demonstrates that the impact of processes occurring at the land surface is not constrained to the lower CBL but extends up to the interfacial layer and the lower troposphere. With respect to the choice of the LSM, the discrepancies in simulating a diurnal change of the humidity profiles are even more significant at the interfacial layer than close to the land surface. This indicates that the representation of land surface processes has a significant impact on the simulation of mixing properties within the CBL. Key Points: DIAL measurements convenient for the model evaluation and the CBL study The convective PBL higher and drier with NOAH‐MP Soil‐vegetation‐atmosphere coupling in WRF stronger toward land